Development of a patient-specific finite element model of the transcatheter aortic valve implantation (TAVI) procedure - Shirzadi, Mohammad Mehdi (Department of Mechanical Engineering, 2017)
Transcatheter Aortic Valve Implantation (TAVI) is a procedure developed for replacing the defective aortic valve of a patient as an alternative to open heart Surgical Aortic Valve Replacement (SAVR). In the TAVI procedure a prosthetic valve, which is assembled on to a stent, is crimped and delivered to the patient's aortic root site through several available percutaneous means. The percutaneous nature of TAVI, which is its core advantage in comparison to other SAVR procedures, can however also be its main disadvantage. This is due to lack of direct access to the calcified leaflets, and hence reliance on the host tissue for the proper positioning and anchorage of the deployed prosthetic valve. Therefore, it is desired to have a preoperative quantitative understanding of patient-specific biomechanical interaction of the stent and the native valve to be able to maximise the chance of success of the procedure. The aim of this study was to develop a patient-specific Finite Element (FE) model of the Transcatheter Aortic Valve Implantation (TAVI) procedure for two patients, using a model of the 23 mm percutaneous prosthetic aortic valve developed by Strait Access Technologies (SAT), for the purpose of its post-operative performance. In this regard, the image processing software ScanIP was used to extract the 3D models of the patient-specific aortic roots and leaflets from the provided Multi-Slice Computer Tomography (MSCT) images of the patients. An anisotropic hyperelastic material model was implemented for the roots and leaflets, using two and one families of collagen fibres for their tissues respectively. The stent is made of a cobalt-chromium alloy and its mechanical response was modelled as an isotropic elastoplastic material, with a linear elastic initial response, followed by plastic behaviour with isotropic hardening. The prosthetic leaflets are made of polymer and were modelled as an isotropic hyperelastic material, using the provided experimental test data. The results for the first patient showed that the stent maintained its structural integrity after deployment, and successfully pushed the native leaflets back to keep the aortic root clear of all impediments. No obstruction of the coronary ostia was observed, and prosthetic leaflets were seen to function normally. The stent radial recoil was calculated to be between 2 to 4.28 % after deployments. Its foreshortening was calculated to be approximately 20%. The stent was observed to move back and forth by approximately 3 mm in the last simulation step in which cardiac cycle pressure were applied to the aortic root and prosthetic leaflets. Also, two openings were observed between the stent and aortic root wall during this simulation step, which indicates the possibility of paravalvular leakage. From the second patient simulation, it was observed that the 23 mm stent was not a good choice for this patient, and will cause severe damage or tissue tearing. The maximum principal stress in the aortic root and valve tissues were observed to follow approximately the defined collagen fibre directions.